1995
DOI: 10.1017/s0021859600084458
|View full text |Cite
|
Sign up to set email alerts
|

Response of broilers to dietary levels of thevetia cake

Abstract: SUMMARYTwo experiments done at the University of Ilorin, Nigeria, in 1992/93 investigated the effects of dietary levels of thevetia cake on the performance and nutrient retention of broilers. In Expt 1, dayold broiler chicks were fed either a control diet or diets containing 5, 10 or 15% thevetia cake during a 4-week period. In Expt 2, day-old broiler chicks were fed a standard diet until 4 weeks of age and were then switched to diets containing 0, 5, 10 or 15% thevetia cake. Inclusion of thevetia cake in broi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 2 publications
(2 reference statements)
0
4
0
Order By: Relevance
“…Feed elements especially proteins constitute a high component in poultry production cost, as much as 75% for broilers and 65% for layers 1 . Legumes are very important sources of protein and lipid in animal nutrition though their use is limited by the presence of antinutritional factors.…”
Section: Introductionmentioning
confidence: 99%
“…Feed elements especially proteins constitute a high component in poultry production cost, as much as 75% for broilers and 65% for layers 1 . Legumes are very important sources of protein and lipid in animal nutrition though their use is limited by the presence of antinutritional factors.…”
Section: Introductionmentioning
confidence: 99%
“…Thevetia cake contains 48% protein content with fat extraction, but Atteh (1995). According, 6 it is dangerous for broilers and needs to be processed further before it can be utilised efficiently as a part of animal feed.…”
Section: Description Of the Plantmentioning
confidence: 99%
“…The oil hydrolysed to give 64% oleic, 6.3% linoleic, 17% palmitic, 11.8% stearic and 0.4% arachidonic acids [1]. Studies have shown that crude protein content of defatted seed of seed cake ranges from 42.79 to 47.50/100 g while that of crude lipid ranges from 4.40 to 4.80/100 g [17][18][19].…”
Section: Introductionmentioning
confidence: 99%